Factors hindering export performance in Botswana: a focus on SMMEs - Molefe, Gloria (My University, 2020)
The purpose of this study was to quantitatively examine the export barriers hindering export performance by Small, Medium and Micro Enterprises (SMMEs) in Botswana. The study focused on SMMEs as defined by the Policy on Small, Medium and Micro Enterprises in Botswana. An online survey through Qualtrics platform was administered to collect data from Botswana SMMEs that were identified through consultation of various sources of firm listings on SMMEs. A total of 122 responses were analysed and further tabulated. The findings revealed that knowledge barriers, internal resource barriers and procedural barriers negatively impacted export performance in Botswana. In other words as these barriers increase firms perform poorly in their exports. The findings of this study must be viewed taking into consideration that not all export barriers were exploited. Another limitation was that this was a cross sectional study and time constrained data collection. Export performance was measured using perceived indicators. In the context of future studies, it would be advisable to conduct a qualitative study so that SMMEs can outline what they perceive as barriers than be confined to the research instrument provided. The stage of exporting should be taken into consideration as well. The findings of this study can be used by firms to gauge their positions in term of export readiness and designing strategies on how to eliminate the barriers and improve their performance; they provide policy makers with empirical information hence guidelines on developing focused strategies especially education programs that equip firms with knowledge on potential export markets and opportunities available and researchers can build more theoretical knowledge on the relationship between these export barriers and export performance. The study generally confirms literature but offers original insights from Botswana context.
A research report submitted n partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Export barriers; Export performance; Small; Medium and Micro Enterprises; Botswana; SDG-8: Decent work and economic growth